Comparison of the fabrication methods, formation dynamics, structure, and delivery performance of solid nanoparticles and hollow layer-by-layer edible/biodegradable nanodelivery systems - Turasan, Hazal; Bonilla, Jose; Bozkurt, Fatih; Maldonado, Luis; Li, Xingfei; Yilmaz, Tuncay; Sadeghi, Rohollah; Kokini, Jozef (WILEY, 2020)
Aim This article summarizes and reviews recent studies on nanoparticulation of solid and hollow nanoparticles using edible proteins and carbohydrates from plant and animal origin and shares new research conducted in our laboratory on fabrication of biopolymer-based nanodelivery systems. Methods We compare the properties of nanoparticles fabricated using desolvation, coacervation, and layer-by-layer assembly. The parameters affecting the morphological and physical states of the nanodelivery systems as well as their abilities to encapsulate bioactive compounds, and the mechanisms of the nanoparticulation process are discussed in detail. Results The article offers methods that need to be used with each nanoparticulation technique along with key characterization data obtained. The effect of varying a wide range of parameters on particle size, size distribution, morphology, effect of solvents and non-solvents, effect of surface charge of polyelectrolytes, effect of fabrication conditions are presented. Conclusions We believe the article gives enough detail to give the reader useful information related to the performance of all the different nanoparticles studied in our laboratory over the last 6 years. Practical applications Biopolymer based nanodelivery systems presented in this article, have great potential to be used in the nutraceutical, food, pharmaceutical industries as well as agriculture. The biodegradable and edible nature of these nanodelivery systems make them safe for incorporating into food and nutraceutical materials, because, the biopolymers used in their fabrication are biocompatible polymers of food origin that are generally recognized as safe (GRAS) (Food and Drug Administration, The Daily Journal of the United States Government, 2016). Therefore, use of edible polymer-based nanoparticles would be safer and less toxic and consequently better for all these industries. For example, in the food industry, antioxidant compounds can be encapsulated which would then be incorporated into packaging materials and that would help maintain freshness and good quality and would prevent oxidative deterioration of foods to increase shelf life. Pesticides and insecticides can also be encapsulated in these nanodelivery systems for agricultural applications. Because they are biodegradable and originated from natural biopolymers, their impact on the environment and the quality of the soil would be minimized compared to current applications that use some burdensome chemicals. Biopolymer based nanodelivery systems would also be of high interest for the pharmaceutical industry. Through the efficacy and extra stability gained with encapsulation, drugs and bioactives would be better protected from the acidic environment of the stomach and be released more controllably in the intestines. Further functionalization of nanodelivery systems with recognition elements, such as antibodies or aptamers, would enable more specifically targeted delivery.
Keywords: ENCAPSULATION; CURCUMIN; MECHANISM; Engineering; Food Science & Technology